Bidirectional needs assessment of otolaryngology–head and neck surgery short‐term surgical trips to Ethiopia and Kenya. Issue 1 (25th January 2023) - Chweya, Cynthia M.; Ryder, C. Yoonhee; Fei‐Zhang, David J.; Green, Katerina J.; Zemene, Yilkal; Okerosi, Samuel; Wiedermann, Joshua P.
Abstract: Objectives: To create an otolaryngology‐specific needs assessment tool for short‐term global surgical trips and to describe our findings from its implementation. Methods: Surveys 1 and 2 were developed based on a literature review and disseminated to Low‐Middle Income (LMIC) hosting institutions in Kenya and Ethiopia and to High‐Income surgical trip participants (HIC), respectively. Respondents were otolaryngologists identified online, through professional organizations, and by word‐of‐mouth, who had participated in a surgical trip of <4 weeks. Results: HIC and LMIC respondents shared similar goals of expanding host surgical skills through education and training while building sustainable partnerships. Discrepancies were identified between LMIC desired surgical skills and supply needs and HIC current practices. Microvascular reconstruction (17.6%), advanced otologic surgery (17.6%), and FESS (14.7%) were most desired skills and high‐demand equipment needs were FESS sets (89%), endoscopes (78%), and surgical drills (56%). Frequently taught techniques included advanced otologic surgery (36.6%), congenital anomaly surgery (14.6%), and FESS (14.6%) with the largest gap between LMIC‐need and HIC‐offerings being in microvascular reconstruction (17.6% vs. 0%). We also highlight the discrepancy in expectations of responsibility for trip logistics, research, and patient follow‐up. Conclusion: We created and implemented the first otolaryngology‐specific needs assessment tool in the literature. With its implementation in Ethiopia and Kenya, we were able to identify unmet needs as well as attitudes and perceptions of LMIC and HIC participants. This tool may be adapted and utilized to assess specific needs, resources, and goals of both host and visiting teams to facilitate successful global partnerships. Level of Evidence: Level VI. Abstract : We described and implemented the first otolaryngology‐specific bidirectional needs assessment. Surveys were disseminated through the relevant otolaryngology communities in the HIC and LMIC. Our results revealed similarities between the goals and experiences of the HIC and LMIC; however, there was disconcordance identified in expectations of logistical and research management as well as LIC needs versus HIC offerings.